Water accounting plus (WA+) - a water accounting procedure for complex river basins based on satellite measurements - Karimi, Poolad; Bastiaanssen, Wim G.M.; Molden, David J. (Copernicus GmbH, 2013)
Coping with water scarcity and growing competition for water among different sectors requires proper water management strategies and decision processes. A prerequisite is a clear understanding of the basin hydrological processes, manageable and unmanageable water flows, the interaction with land use and opportunities to mitigate the negative effects and increase the benefits of water depletion on society. Currently, water professionals do not have a common framework that links depletion to user groups of water and their benefits. The absence of a standard hydrological and water management summary is causing confusion and wrong decisions. The non-availability of water flow data is one of the underpinning reasons for not having operational water accounting systems for river basins in place. In this paper, we introduce Water Accounting Plus (WA+), which is a new framework designed to provide explicit spatial information on water depletion and net withdrawal processes in complex river basins. The influence of land use and landscape evapotranspiration on the water cycle is described explicitly by defining land use groups with common characteristics. WA+presents four sheets including (i) a resource base sheet, (ii) an evapotranspiration sheet, (iii) a productivity sheet, and (iv) a withdrawal sheet. Every sheet encompasses a set of indicators that summarise the overall water resources situation. The impact of external (e.g., climate change) and internal influences (e.g., infrastructure building) can be estimated by studying the changes in theseWA+ indicators. Satellite measurements can be used to acquire a vast amount of required data but is not a precondition for implementingWA+ framework. Data from hydrological models and water allocation models can also be used as inputs to WA+.